Studi Kelayakan Bisnis Pada Produk Phees Pro - Amatu Dzil Izza Tisaini; mochamad reza adiyanto (Management Department of Economics and Business Of Trunojoyo Madura University, 2026)
The Indonesian aquaculture industry faces major challenges in the form of high feed costs that dominate the production cost structure and low fish farming efficiency. These conditions demand feed innovations that not only increase productivity but are also commercially viable. This study aims to analyze the business feasibility of PHEES PRO, a fish feed induced by probiotic bacteria, from a legal, market, and financial perspective. The theoretical basis used includes the concept of business feasibility studies, institutional theory, market structure, investment theory, and the Total Addressable Market (TAM), Serviceable Available Market (SAM), and Serviceable Obtainable Market (SOM) approaches. The research method applied is a descriptive qualitative and quantitative approach with data collection techniques through interviews, observation, documentation, and secondary data analysis. The legal aspect analysis is conducted by reviewing business legality, regulatory compliance, and the product's position on the Negative Investment List. The market aspect is analyzed through demand forecasting and calculations of TAM, SAM, and SOM. Meanwhile, the financial aspect is analyzed using Net Present Value (NPV) indicators, Profitability Index (PI), and sensitivity analysis. The research results indicate that PHEES PRO has potential market prospects, supported by the increasing demand for high-quality and efficient fish feed. Financially, this product is deemed feasible with a positive NPV and PI greater than one, and is relatively resilient to changes in key variables. Therefore, it can be concluded that the PHEES PRO business is feasible to develop and has sustainable potential in the Indonesian aquaculture sector.